2022
DOI: 10.1088/1674-4527/ac9c4b
|View full text |Cite
|
Sign up to set email alerts
|

A Possible 250 s X-Ray Quasi-periodicity in the Fast Blue Optical Transient AT2018cow

Abstract: The fast blue optical transients (FBOTs) are a new population of extragalactic transients of unclear physical origin. A variety of mechanisms have been proposed including failed supernova explosion, shock interaction with a dense medium, young magnetar, accretion onto a compact object, and stellar tidal disruption event, but none is conclusive. Here we report the discovery of a possible X-ray quasi-periodicity signal with a period of ~250 second (at a significance level of 99.76%) in the brightest FBOT AT2018c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In 2018, a particularly intriguing FBOT-AT 2018cowwas discovered by the Asteroid Terrestrial-impact Last Alert System (Prentice et al 2018;Smartt et al 2018) in the starforming dwarf galaxy CGCG 137-068 (z = 0.0141) that rose to a peak brightness M ∼ −22, similar to superluminous SNe, in 2 days. Multiwavelength follow-up observations (e.g., Rivera Sandoval et al 2018;Ho et al 2019;Huang et al 2019;Kuin et al 2019;Margutti et al 2019;Perley et al 2019;Bietenholz et al 2020;Pasham et al 2021;Xiang et al 2021) revealed an array of peculiar properties, including (i) bright millimeter radio emission associated with mildly relativistic outflow (v ∼ 0.1c) in CSM (Ho et al 2019); (ii) bright X-ray emission with signs of quasiperiodic oscillation (QPO) indicative of a central engine (Rivera Sandoval et al 2018;Kuin et al 2019;Margutti et al 2019;Pasham et al 2021;Zhang et al 2022); (iii) rapidly fading optical emission with a persistent blue color and a receding photosphere (Margutti et al 2019;Perley et al 2019;Xiang et al 2021); (iv) a separate IR component likely associated with dust (Perley et al 2019;Metzger & Perley 2023); (v) a sudden transition from broad to intermediate-width spectral features ∼15-20 days after peak, suggesting multiple (possibly asymmetric) thermal emission components (Margutti et al 2019;Perley et al 2019;Xiang et al 2021); and (vi) flashes of high optical polarization that further support an asymmetric configuration (Maund et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2018, a particularly intriguing FBOT-AT 2018cowwas discovered by the Asteroid Terrestrial-impact Last Alert System (Prentice et al 2018;Smartt et al 2018) in the starforming dwarf galaxy CGCG 137-068 (z = 0.0141) that rose to a peak brightness M ∼ −22, similar to superluminous SNe, in 2 days. Multiwavelength follow-up observations (e.g., Rivera Sandoval et al 2018;Ho et al 2019;Huang et al 2019;Kuin et al 2019;Margutti et al 2019;Perley et al 2019;Bietenholz et al 2020;Pasham et al 2021;Xiang et al 2021) revealed an array of peculiar properties, including (i) bright millimeter radio emission associated with mildly relativistic outflow (v ∼ 0.1c) in CSM (Ho et al 2019); (ii) bright X-ray emission with signs of quasiperiodic oscillation (QPO) indicative of a central engine (Rivera Sandoval et al 2018;Kuin et al 2019;Margutti et al 2019;Pasham et al 2021;Zhang et al 2022); (iii) rapidly fading optical emission with a persistent blue color and a receding photosphere (Margutti et al 2019;Perley et al 2019;Xiang et al 2021); (iv) a separate IR component likely associated with dust (Perley et al 2019;Metzger & Perley 2023); (v) a sudden transition from broad to intermediate-width spectral features ∼15-20 days after peak, suggesting multiple (possibly asymmetric) thermal emission components (Margutti et al 2019;Perley et al 2019;Xiang et al 2021); and (vi) flashes of high optical polarization that further support an asymmetric configuration (Maund et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…One may speculate that there could be a chance that a straggling IMBH or SMBH was left behind from this dynamical interaction. Another example is the low-frequency X-ray QPO discovered by Zhang et al (2022) from XMM-Newton and Swift observations. Zhang et al (2022) suggested that the low-frequency QPO is more consistent with IMBHs and SMBHs, and the NICER QPO limit could be relaxed by introducing the IMBH or SMBH in a compact binary.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The result is that the magnetization in the nebula may be very low, which is necessary to explain the the observed late-time steepening of superluminous SN optical light curves (Vurm & Metzger 2021). It should also be emphasized that AT2018cow has many other peculiar observational properties that are not discussed in the present work, such as high-amplitude quasiperiodic oscillation of AT2018cowʼs soft X-rays with a frequency of 224 Hz (Pasham et al 2021); possible 250 s X-ray quasiperiodicity (Zhang et al 2022); luminous UV emission detected 2-4 yr after the explosion (Sun et al 2022;Chen et al 2023); and persistent X-ray emission at the location of AT2018cow ∼3.7 yr after discovery (Migliori et al 2023). It is a great challenge to explain all these peculiar observational properties of AT2018cow based on the millisecond magnetar as the central engine and there is still a lot of work to be done.…”
Section: Possible Progenitor Modelmentioning
confidence: 71%
“…Slowly decaying, luminous (L > 10 7 L ☉ ) UV emission years after discovery has been recently reported by Sun et al (2022Sun et al ( , 2023, Chen et al (2023aChen et al ( , 2023b, Inkenhaag et al (2023), andMummery et al (2024), and similarities have been noted with radiation powered by accretion processes on compact objects. Along the same lines, a high-frequency (224 Hz) quasi-periodic oscillation (QPO) feature in the X-ray timing properties of AT 2018cow supports the presence of a compact object, either an NS or a BH with mass M < 850 M e (Pasham et al 2021; but see also Zhang et al 2022). While no evidence was found for a long-lived relativistic jet such as those of GRBs (Bietenholz et al 2020;Mohan et al 2020), panchromatic observations of AT 2018cow further indicated a complex geometry that strongly departs from spherical symmetry, as was directly confirmed by the very large optical polarization (∼7%) at early times (Maund et al 2023).…”
Section: Introductionmentioning
confidence: 81%